Study of asymmetrical magnetic coupled resonant wireless power transmission system - FAN Yingjie; ZHANG Kairu; ZHANG Linlin; WANG Yi; DI Dongzhao (Gong-kuang zidonghua, 2016)
According to equivalent model of asymmetrical magnetic coupled resonant wireless power transmission system, a view was pointed out that magnetic coupled resonant wireless power transmission which could maintain long distance transmission at resonance frequency was a special case of magnetic coupled inductive wireless power transmission. Methods of restraining frequency splitting were given, namely changing offset angle and radial distance of axial direction of transmitting coil and receiving coil to reduce mutual inductance coefficient and improve peak voltage of the receiving coil. Finally, experimental platform of asymmetrical magnetic coupled resonant wireless power transmission system was built and the experimental results verified correctness of theoretical analysis.